The Knowledge Management System of a State Loss Settlement - Amalia Rahmawati; Irman Hermadi; Rein Suadamara (Institute of Advanced Engineering and Science, 2015)
The knowledge management is a model involving the information system in the knowledge processing. Tim Penyelesaian Kerugian Negara (TPKN) is one of sources of information related to the state loss settlement, so it needs the development of knowledge management system on the state loss settlement to ease the users when looking for the references of knowledge as completely as possible, accurately, and quickly. This research aims to develop the system of knowledge management on the state loss in LAPAN (SIMAPKLA). The used research methodology is Knowledge Management System Life Cycle (KMSLC). The tacit, explicit knowledge is taken from the experts and it is stored in the Knowledge Base (KB). The design model uses the approach with the orientation of object and implementation with Yii Framework and blackbox testing. The menu on this system includes home, about us, dictionary, news, meeting schedulles, knowledge about state loss, e-document, progress, and forum. Based on a series of tests, in the aspect of functionality, this system is suitable and useful to share knowledge and know the development of state loss settlement. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7388